2009
DOI: 10.1016/j.bmc.2008.10.057
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and evaluation of electron-rich curcumin analogues

Abstract: The natural product curcumin has long been recognized for its medicinal properties and is utilized for the treatment of many diseases. However, it remains unknown whether this activity is based on its presumably promiscuous scaffold, or if it results from the Michael acceptor properties of the α,β-unsaturated 1,3-diketone moiety central to its structure. To probe this issue, electron-rich pyrazole and isoxazole analogues were prepared and evaluated against two breast cancer cell lines, which resulted in the id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
67
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(76 citation statements)
references
References 22 publications
5
67
0
2
Order By: Relevance
“…Several studies revealed that curcumin and its congeners manifest antiproliferative activity against various cancers, however, the actual mechanism of the antitumor potential of curcuminoids are still far from being under-stood [13]. With this in mind, it was reported that such compounds of Michael acceptor-type could inhibit cancer cell proliferation in vitro and in vivo via promotion of apoptosis in cancer cells by suppressing cyclin D and endothelial growth factor receptor (EGFR) function, while simultaneously decreasing levels of phosphokinase B (AKT), c-myc, and phospho-AKT (pAKT) [14]. In one of the more significant findings on the anticancer activity of compounds inspired by curcumin, Adams et al [15] announced the superior activity of 2,6-bis(2-fluorobenzylidene)piperidone (EF24) in anti-angiogenesis, cell cycle arrest, and apoptosis of cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies revealed that curcumin and its congeners manifest antiproliferative activity against various cancers, however, the actual mechanism of the antitumor potential of curcuminoids are still far from being under-stood [13]. With this in mind, it was reported that such compounds of Michael acceptor-type could inhibit cancer cell proliferation in vitro and in vivo via promotion of apoptosis in cancer cells by suppressing cyclin D and endothelial growth factor receptor (EGFR) function, while simultaneously decreasing levels of phosphokinase B (AKT), c-myc, and phospho-AKT (pAKT) [14]. In one of the more significant findings on the anticancer activity of compounds inspired by curcumin, Adams et al [15] announced the superior activity of 2,6-bis(2-fluorobenzylidene)piperidone (EF24) in anti-angiogenesis, cell cycle arrest, and apoptosis of cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…To circumvent this limitation, several approaches were carried out, including the synthesis of curcumin analogues [4,12,13]. Curcumin derivatives were synthesised in order to overcome the pharmacokinetics limitations, with the hope to preserve the same safety profile.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11] During the past few decades, great attention has been paid to structure modification to overcome these problems, and various novel structural analogs of curcumin have been designed for screening. [12][13][14] Dimethoxycurcumin (DMC; Figure 1) is a kind of lipophilic analog of curcumin with all the phenolic hydroxyl groups methylated, and can be easily obtained by synthetic or semi-synthetic methods. 15,16 A variety of experimental studies based on cells and animals have showed that such structural modifications brought about great improvement of DMC in chemical and metabolic stability, as well as anti-inflammatory and anti-tumor activities.…”
Section: Introductionmentioning
confidence: 99%